Strengthening Fraud Prevention: The Role of Islamic Work Ethics, Islamic Corporate Governance, and Compensation as a Moderating Factor - Egi Gumala Sari; Qonitatun Luthfiyah; Ahmad Athaillah (Indonesian Journal of Islamic Economics and Business, 2026)
This research aims to obtain empirical evidence about the influence of Islamic Work Ethics and Islamic Corporate Governance on Fraud Prevention with Compensation as a moderation variable. This research uses a quantitative type of research. This research was conducted using a questionnaire distributed to leaders and staff of Islamic Financial Institutions in Bekasi, namely as many as 200 questionnaires distributed via email and social media. Each questionnaire distributed contains 81 statements for respondents to answer. From the distribution of the questionnaire, 112 respondents provided answers. To get the results of this research, researchers used PLS SEM Version 3.0. These results of this research found that Islamic Work Ethics has a positive effect and significant effect on Fraud Prevention, Islamic Corporate Governance has a positive effect and not significant effect on Fraud Prevention, Compensation cannot strengthen the relationship between Islamic Work Ethics and Fraud Prevention and Compensation cannot strengthen the relationship between Islamic Corporate Governance and Fraud Prevention. This research has several limitations that should be considered when interpreting the results. First, the research sample does not represent the characteristics of the industry because it only includes a small proportion of Islamic financial institutions. Second, because the compensation structure of Islamic financial institutions varies, the moderating role is affected by inconsistencies in the application of compensation. Finally, cross-sectional studies may not be able to capture long-term changes in the influence of IWE and ICG on fraud prevention. Implications for future research include the need to expand the sample to include different types of Islamic financial institutions, such as banks, cooperatives, and Islamic insurance from different geographical locations to improve the generalizability of the results